The Oxford Handbook of 4E Cognition 2018
DOI: 10.1093/oxfordhb/9780198735410.013.39
|View full text |Cite
|
Sign up to set email alerts
|

Mindshaping

Abstract: According to consensus, distinctively human social accomplishments rely on an individual, neurally implemented capacity to represent the mental states of others, typically called “mindreading” or “theory of mind.” On this view, early humans and their immediate precursors moved beyond typical primate social arrangements, e.g., by engaging in large-scale cooperative projects with individuals of whom they have scant personal knowledge, in virtue of developing a theory of mind. This chapter articulates, explores, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 0 publications
0
22
0
1
Order By: Relevance
“…Chs. 2-3;Zawidzki 2013). Other non-human animals, e.g., crows, also have a capacity to develop rudimentary "culture" in the sense that they develop skills and tools that are passed from one generation to the next by learning rather than by becoming innate.…”
Section: Socialitymentioning
confidence: 99%
See 1 more Smart Citation
“…Chs. 2-3;Zawidzki 2013). Other non-human animals, e.g., crows, also have a capacity to develop rudimentary "culture" in the sense that they develop skills and tools that are passed from one generation to the next by learning rather than by becoming innate.…”
Section: Socialitymentioning
confidence: 99%
“…They, in turn, may just follow the direction she took when she set off, thus learning the route without direct instruction. This can be regarded as a kind of apprenticeship that is common to social learning: take a cue from the more knowledgeable around you, figure it out as best you can how to accomplish the task based on their lead, and await correction (from the circumstances or from those more knowledgeable), when you go wrong (Sterelny 2013; on social reproduction, see also Zawidzki 2013;McGeer 2007).…”
Section: Socialitymentioning
confidence: 99%
“…Zawidzki has suggested that Dennett’s strategy is to deflate and revise our manifest concepts of intentionality and consciousness in terms of publicly observable patterns of behavior. As intersubjectively verifiable phenomena, describable from the intentional stance and captured by heterophenomenology, they are, then, arguably easier to reconcile with the scientific image, i.e., what standard science accepts and rules out ( Zawidzki, 2007 , p. 154–156; cf. Dennett, 1987 , p. 25).…”
Section: Strong and Weak Skepticismmentioning
confidence: 99%
“…Dennett denies the existence of qualia so defined as objectively undetectable, intersubjectively untestable, and, thus, incompatible with standard science. Hence, Dennett regards investigating consciousness scientifically in these terms impossible (see Zawidzki, 2007 , p. 167–169). Whether Dennett’s self-avowed eliminative materialism and verificationism about qualia amounts to denying conscious experience conceived in less contentious terms is debatable 20 .…”
Section: Strong and Weak Skepticismmentioning
confidence: 99%
See 1 more Smart Citation